Pemikiran Filosofis Pendidikan Islam (Esensialisme) - Akbarizan Akbarizan (MUI Kota Pekanbaru, 2023)
Essentialism represents one of the branches within the realm of educational philosophy. The emergence of this perspective can be traced back to a response against the absolutist and dogmatic tendencies of medieval symbolism. Subsequently, it formulates a structured and all-encompassing understanding of humanity and the universe, tailored to the contemporary demands. The essentialist viewpoint in education asserts that a foundational approach, contrasting with a wholly flexible stance, can serve as a foundation for cultivating a steadfast and unwavering outlook, one that is less prone to fluctuations and inconsistency. Consequently, education should be grounded in enduring values that promote stability, have stood the test of time, exhibit clarity, and are deliberately chosen.The essentialist philosophy of education aims to reintroduce a return to traditional culture. Advocates of this philosophy hold the belief that ancient cultures possess numerous virtues capable of benefiting the progression of humanity. Their emphasis is on reverting to cultural practices that have existed since the inception of human civilization, with a primary focus on the cultural advancements that transpired during the Renaissance period, spanning the 11th to 14th centuries AD. The Renaissance was marked by significant efforts to rekindle the realms of science, art, and classical culture, particularly those hailing from the eras of ancient Greece and Rome. In contrast, the Islamic philosophical perspective on education and the concept of essentialism exhibits distinctions. These differences arise from varying interpretations concerning the interrelation between God, human beings, and the natural environment. The philosophical underpinnings of Islamic education find their foundation within the core concepts of Islam, encompassing the Quran and Hadith, as well as insights from distinguished Islamic scholars and thinkers.